2008
DOI: 10.1007/s10745-008-9170-9
|View full text |Cite
|
Sign up to set email alerts
|

Conservation with a Gun: Understanding Landowner Attitudes to Deer Hunting in the Scottish Highlands

Abstract: Conservation conflicts are often difficult to resolve due to a combination of poorly defined property rights, inadequate funding, high transaction costs, and contrasting value systems among stakeholders. This paper explores these barriers to collaboration in the context of the emerging deer crisis in the Scottish Highlands, where deer numbers are now higher than at any time in recorded history. In particular we explore the potential role of recreational hunting in the government's strategy to contain rising de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 25 publications
(22 reference statements)
1
29
0
Order By: Relevance
“…Traditional stalking involves minimum disturbance on deer movements. Male movement rather than female movement is more likely to be disturbed as hunting occurs in the summer months when the presence of people in public access areas is higher (MacMillan & Leitch 2008). Results are also unlikely to be the result of translocations of individuals between estates.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional stalking involves minimum disturbance on deer movements. Male movement rather than female movement is more likely to be disturbed as hunting occurs in the summer months when the presence of people in public access areas is higher (MacMillan & Leitch 2008). Results are also unlikely to be the result of translocations of individuals between estates.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of the general public showed strong support for deer abundance control to avoid threats to human health or safety or environmental damage, but control was judged less acceptable when it was aimed at reducing aesthetic impacts or personal property damage (Fulton et al ., ). Among Scottish recreational hunters, resistance to regulating soaring deer populations, a reluctance rooted in hunting tradition or personal preferences, was reinforced by antipathy to conservationists (MacMillan & Leitch, ).…”
Section: Challenges and Ways Forwardmentioning
confidence: 99%
“…However, this action raised a question with regard to the extent to which estate owners and managers might be willing to add value to their products and services, especially when it is difficult to recoup costs, or if an addition in value were to lead to an increase in the number of visitors to the estate. MacMillan and Leitch (2008) found that private landowners have "little enthusiasm for attracting new clients" as they often value their privacy and personal opportunity to hunt more highly than income (p. 481).…”
Section: 'Broadening Options': Adding Value and Increasing Flexibilitymentioning
confidence: 99%